Effect of the incorporation of polysaccharides from green alga Bryopsis plumosa on beef sausages quality: Polysaccharides addition on sausages quality - Ghariani, Marwa; Ben Saad, Hajer; Hamzaoui, Asma; Ajela, Marwa; Hilali, Abderraouf; Ben Amara, Ibtissem (Cellular and Molecular Biology, 2022)
Maintaining the quality and stability of functional meat products during storage is one of the major challenges of these products. The aim of this study was to evaluate the potential of polysaccharides extracted from green alga Bryopsis plumosa as a new natural additive in the formulation of beef sausages. In order to evaluate the impact of the incorporation of polysaccharides in beef sausages formulation, the physico-chemical, microbiological, and antioxidant properties were investigated during 12 days of storage at 4°C. Obtained data illustrated that the addition of this polymer in the formulation of beef sausages leads to a distinct antioxidant activity during 12 days of storage (4°C) with lower values in terms of lipid peroxidation compared to untreated samples. In addition, samples formulated with polysaccharides reduced the oxidation of Myoglobin, which consequently improved the color stability of meat during refrigerated storage. Furthermore, as compared to standard formulation, the addition of polysaccharides appears to have interesting antimicrobial potential that maintains sausage quality within a shelf life of 12 days. In conclusion, our results prove the efficiency of polysaccharides in providing more hygienic and safer meat products, which may suggest that PS could be used as a natural additive in functional foods.